2012
DOI: 10.1353/asi.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Complexity and Modern Traits in the Philippine Upper Palaeolithic

Abstract: Behavioral modernity has been a widely neglected topic for Southeast Asia’s prehistory. Evidence of modern packages or even traits is basically absent in the Palaeolithic assemblages. This absence has considerably influenced the discussion of hominid behavior and their cultural and cognitive abilities. In a case study on terminal Pleistocene artifacts from Ille Cave on Palawan Island, indications of the presence of several items of the modern trait list, foremost the first evidence of hafted lithic tools and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…A technological comparison with assemblages recovered from several other Holocene caves and rock-shelters in central Palawan, such as Guri and Pilanduk (Fox 1970;1978;Kress 1979;Pawlik & Ronquillo 2003), suggests continuation of identical traditions from the Late Pleistocene into the Holocene, without any obvious innovation. Similar simple unretouched flakes have been identified in Ille Cave, northern Palawan, dating to the Terminal Pleistocene and Early to Mid Holocene (Lewis et al 2008;Pawlik 2012;Szabó et al 2004), in Late Pleistocene deposits at Callao Cave in Northern Luzon, dated on charcoal to c. 30,000 cal. bp (Mijares 2007), and at the nearby Minori (Mijares 2002) and Vito (Fuentes 2015) Caves, dating to c. 5500-5000 cal.…”
Section: Lithic Technologiessupporting
confidence: 67%
See 1 more Smart Citation
“…A technological comparison with assemblages recovered from several other Holocene caves and rock-shelters in central Palawan, such as Guri and Pilanduk (Fox 1970;1978;Kress 1979;Pawlik & Ronquillo 2003), suggests continuation of identical traditions from the Late Pleistocene into the Holocene, without any obvious innovation. Similar simple unretouched flakes have been identified in Ille Cave, northern Palawan, dating to the Terminal Pleistocene and Early to Mid Holocene (Lewis et al 2008;Pawlik 2012;Szabó et al 2004), in Late Pleistocene deposits at Callao Cave in Northern Luzon, dated on charcoal to c. 30,000 cal. bp (Mijares 2007), and at the nearby Minori (Mijares 2002) and Vito (Fuentes 2015) Caves, dating to c. 5500-5000 cal.…”
Section: Lithic Technologiessupporting
confidence: 67%
“…Residues of tree resins on the implements from Ille are also similar in morphology to the resinous adhesives applied to the composite artefacts from Niah (Barton et al 2009;Pawlik 2012). Simple flakes were also used to process red pigments and resins (Pawlik 2012), and to work with resinous wood or pieces of tree resin (Reynolds et al 2013, 155). Interestingly, also in Ille, a mixture of red pigment and resin was used as appliqué on Conus shell discs dated to 4800-4200 cal.…”
Section: Lithic Technologiesmentioning
confidence: 99%
“…Technology in this region is often labeled as informal and even expedient, without any preparations as opposed to curated tools [80], and not exhibiting any visible development. From the stone tool assemblages of the late Pleistocene, the lack of diagnostic features carried on even until the late Holocene and historical periods [81][82][83][84][85][86]. In general, results from a techno-typological approach may therefore not reflect the actual level of technological development in the region and thus other approaches are deemed necessary.…”
Section: Development Of Lithic Technology and Lithic Tool Use In Islamentioning
confidence: 99%
“…Although stone tool assemblages in ISEA are generally characterized by the production and use of unretouched flake tools, it does not necessarily mean that the prehistoric technology in the region was less complex. In several sites in ISEA, the existence of composite technologies have been identified that employed unretouched flakes by attaching them as insets to shafts with the aid of resinous adhesives, for hunting weapons and also for tools with handles such as knives [32,86,92]. This is another example when a microscopic approach is particularly suitable for addressing current issues in understanding the prehistoric lithic technology of ISEA [32,38,86,93].…”
Section: Development Of Lithic Technology and Lithic Tool Use In Islamentioning
confidence: 99%
“…They note that the Philippine archipelago seems to have been part of a vast maritime network connecting Southeast Asia to Near Oceania, as evidenced by common shell and lithic technologies (i.e. Barton et al, 2009;Mijares, 2006;Neri et al, 2015;Pawlik, 2012;Pawlik et al, 2015) and shared complex burial traditions, including secondary inhumations and cremations (i.e. Detroit, 2006;Lara et al, 2013Lara et al, , 2016Lewis et al, 2008;O'Connor et al, 2017;Szabó et al, 2007).…”
Section: Introductionmentioning
confidence: 99%